A orientação para metas dos gerentes de projeto e a eficiência do projeto e desempenho da equipe de projetos: o papel da orientação empreendedora - Mattos, Marcio Saraiva (2020)
For years, studies on the project manager's contribution to the project's success had a strong focus on Hard skills, however, the number of articles focused on the project manager's soft skills is growing. Studies on an individual's goal orientation, which is a characteristic of the individual, have shown that this characteristic influences the success of projects. This study intends to contribute to research and to practice in project management, by dimensioning the effect of the project manager on the success and performance of projects, according to his goal orientation and the environment, moderated by the entrepreneurial orientation. Based on the observed results, it was possible to verify the positive relationship between orientation towards learning goals and some dimensions of project success, such as team management and project management. Additionally, the goal orientation to avoid difficulties showed a negative relationship with team management.